A Peruvian consensus for the diagnosis and therapy of Mycosis fungoides and Sezary syndrome - Beltrán Gárate, Brady (2009)
Background: Several reviews and guidelines on the management of Mycosis Fungoides (MF) and Sézary syndrome (SS) have been published; however, treatment strategies for patients with MF/SS vary from institution to institution and among countries. There are few phase III trials to support treatment decisions for MF/SS and treatment is often determined by institutional experience. Objetive: In order to summarise the available evidence and review best practices, Peruvian Consensus met in September 2004 to establish guidelines for the diagnosis and treatment of MF/SS. Results:This article reviews hystopatologic, clinic and therapeutic criteria of MF/SS.